The Rights of Citizenship of Children and Adolescents in a single Territory: the triple Amazon Border - Pineda Nebot, Carmen; Pinheiro de Andrade, Herbert Cristhiano; Almeida Olavo, Antônio Vagner (Sociedad e Infancias, 2018)
The objective of this article is to analyze the general situation of the protection of the rights and duties of children and adolescents in Brazil, Colombia and Peru, and to identify the actions of protection of their rights in the triple border constituted by the cities of Tabatinga (BR) , Leticia (CO), and Isla de Santa Rosa (PE). This qualitative research has analyzed documents and legislation related to the rights of children and adolescents of the three countries, as well as the web pages of the three cities. In addition, in-depth interviews were conducted with those responsible for the actions for children and adolescents in the Amazonian tri-border. Given the legal conquest of the rights of citizenship of children and adolescents and a reality of social vulnerability, we point out that the protection of these rights must be faced by means of territorial intersectoral actions. However, in the cities analysed, disarticulated state actions that do not take into account the special territorial situation prevail.